Illocutionary Speech Acts of Articulating Commands in the Movie “Marvels”: An analysis of Linguistics Principles - Skolastika , I Made Perdana; Mahardika, Kadek Wisnu (Journal of Language and Literature Studies, 2024)
Speech acts play a crucial role in human communication, allowing individuals to perform actions through language. The application of speech act is crucial especially in communication because it is an action of communication. Therefore, this study investigates the various forms of illocutionary acts, with a particular emphasis on directive speech acts, as presented in the film "The Marvels" from the Marvel Cinematic Universe. This study uses qualitative methodology to deeply analyze the use of directive speech acts in The Marvels. This qualitative approach is appropriate because it emphasizes a detailed examination of the dialogue, context, and pragmatic functions of language in the narrative. By focusing on the meaning and purpose behind the directive speech acts used by the main characters, this study aims to uncover patterns, relationships, and insights that cannot be easily measured. Utilizing Searle's theory of speech acts, Grice's conversational implicature theory, and the situational context framework proposed by Halliday and Hasan, the research explores the way the characters' dialogues are shaped by these linguistic principles. The analysis focuses on how the context of the dialogue influences the illocutionary force of the characters' interactions, revealing the intricate ways in which meaning is conveyed. The findings highlight the importance of a multidisciplinary approach to understanding communication in film, showing that the study of language within specific contexts can enhance people’s appreciation of character interactions and narrative development. This research contributes to the broader field of linguistic analysis in literature and offers valuable insights for students and scholars.